THE IMPACTS OF DIEGETIC STRATEGIES ON THE LOCALIZATION QUALITY OF GENSHIN IMPACTS' ACHIEVEMENT FEATURES - Nabil Aqib (UIN Raden Mas Said Surakarta, 2024)
The aim of this thesis is to find out how the strategy of achievement on Genshin Impact term is translated from English into Indonesian in video game. This research uses qualitative method to explore the objectives of the research. The researcher collected data through several steps which aims are: to find the translation strategy contained in the video game, to classify and analyze the types of translation strategy from Achievements on Genshin Impact based on Purnomo translation strategy in video games theory, then determine the most dominant type of translation strategy and describe the translation strategy of Genshin Impact and finally concluded the result. The results of this research showed that Purnomo's (2019) proposed strategies for translating video games are used, 149 data were found, classified into the following categories: 2 Abbreviation, 13 Condensation, 13 Omission, 8 Symbolization, 88 Retention, and 25 Mediation. Therefore, the dominant data is Retention, which means that Retention is used to preserve source language words or terms that are considered and accepted conventionally by gamers and become fatal if translated. Based on the analysis, the localization quality assessment reveals that Achievements in Genshin Impact localization achieve a